2018
DOI: 10.3390/su10072274
|View full text |Cite
|
Sign up to set email alerts
|

Financial Aspects of Sustainability: An Evidence from Slovak Companies

Abstract: Business sustainability has been one of the leading topics of the financial management of Slovak companies since the beginning of the millennium. The initially relatively strict link only to environmental aspects has been supplemented by the economic and social dimensions in recent years, under the pressure of the business environment. Examining the link between a company's financial performance and sustainability is addressed in this paper by the financial ratios method and the correlation and linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…The impact of corporate sustainability on stock market returns has been a very common area of research [38], as well as the consequences of sustainability index inclusions and exclusions on corporate values [39][40][41]. Another important area of financial management and sustainability connections is the discussion of the relationship between social and environmental performance and financial performance [42][43][44][45][46][47].…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…The impact of corporate sustainability on stock market returns has been a very common area of research [38], as well as the consequences of sustainability index inclusions and exclusions on corporate values [39][40][41]. Another important area of financial management and sustainability connections is the discussion of the relationship between social and environmental performance and financial performance [42][43][44][45][46][47].…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…Business sustainability, one of the leading topics in financial management, has attracted many concerns in recent years [7]. The primary goal of the business is to maximize the wealth of its shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable finance is strongly linked to financial sustainability, which is related to structural, relational and cognitive aspects that create value for a company [4] and the long-time survival capacity of companies. The link between business sustainability and the financial performance of a firm has been demonstrated by several studies, as reference [5] showed.…”
Section: Introductionmentioning
confidence: 91%